A Place We Call “Home” –International Students in Virtual Context - Zhu, Zheng (Journal of International Students, 2012)
This paper examines how Chinese international students from a public land-grant university used online community to construct their cultural and ethnic identities. The author delves into the question of how online community enables these students to gain successful cultural assimilation. Extending on Baym’s (2000) theoretical framework of online group communication and Mabry’s (1997) critical discussion on constructing virtual identity, this paper offers crucial implications for how online communication forums, such as Bulletin Board System (BBS), evolve into cultural institutions as a result of affiliated members’ increasing reliance on virtual social networking. The cyber communicative practice may deny participating members’ access to authentic human communication and reinforce their negative self-labeling as an unassimilable or unfavorable “other” in a new cultural environment.